Forced Vibrations of Pre-Stressed Sandwich Plate-Strip with Elastic Layers and Piezoelectric Core* - Da Demir, A. (Springer Science and Business Media LLC, 2018)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: sandwich plate-strip; Vibrations in dynamical problems in solid mechanics; Electromagnetic effects in solid mechanics; finite-element method; piezoelectric core; Plates; harmonic force; 7. Clean energy